Favorable Outcome of Severe Poisoning by Snake Green Mamba (Dendroaspis viridis) Clinical Case - A. R. Nasibullina; A. N. Lodyagin; V. A. Vdovin; N. E. Filippova; B. V. Batotsyrenov; S. I. Glushkov (Общая реаниматология, 2019)
This clinical case of acute poisoning due to bite of snake Dendroaspis viridis seems interesting to share because of its rare incidence inRussiaand management peculiarities: the critical care was conducted without specific antidote therapy due to absence of the antidote.The prevailing clinical presentation included signs of toxic myopathy combined with paresis of skeletal and breathing muscles that led to development of acute respiratory failure and metabolic disorders. The processes described were induced by the action of snake poison dendrotoxins featuring the activities of potassium channel blockers and acetyl cholinesterase inhibitors.The proper critical care included conduct of syndrome therapy aimed at maintaining life support systems adequately to condition (replacement of the breathing and circulation functions), antibiotic therapy and desensitizing treatment and metabolic care by administration of drugs characterized by antihypoxant/antioxidant mechanism of action.The comprehensive therapy applied has resulted in a favorable outcome of acute poisoning by snake green mamba without development of possible complications even when the specific antidote drug has not been included into the treatment protocol.